Simulation of the creep and fatigue damages in high-Cr steel components based on a modified becker-hackenberg model - Wang, Jiong; Steinmann, Paul; Rudolph, Jürgen; Willuweit, Adrian (American Society of Mechanical Engineers, Pressure Vessels and Piping Division (Publication) PVP, 2014)
Components of conventional power plants are subject to three potential damage mechanisms and their combination (accumulation) with impact on lifetime considerations: creep, fatigue and ratcheting. Currently, there is a growing need for advanced material models which are able to simulate these damage phenomena and can be implemented effectively within finite-element (FE) codes. This constitutes the basis of an advanced component design. In this work, a constitutive material model, named as the modified Becker-Hackenberg model, is proposed to simulate the thermo-mechanical behavior of high-Cr steel components subject to complex loading conditions. Both creep and viscoplasticity are taken into account in the model, which are viewed as two different kinds of inelastic mechanisms. The key features of the creep strain, i.e., the minimum creep rate and the average creep rupture time, are evaluated by using two Larson-Miller parameters. The cyclic viscoplastic strain is predicted through the conventional Chaboche-type modeling approach, where suitable constitutive evolution equations are adopted to capture the cyclic softening effect, ratcheting effect, time recovery effect and temperature rate effect. All the material parameters involved in this model are identified by using a strategy of stress-range separation. This constitutive model is further implemented in a commercial FE software to simulate the thermo-mechanical behaviors of high-Cr steel components with technologically relevant dimensions. The strain and stress evolution data obtained from the model can be further used for the fatigue damage assessment of high-Cr steel components subject to creep-fatigue interactions. Within an ongoing work, a multiaxial fatigue analyzer is developed to predict the fatigue lifetime of high-Cr steels subject to cyclic loading conditions respectively - in a further step - creep-fatigue interaction.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Constitutive model; Creep; Cyclic viscoplasticity; Finite element simulation; High-Cr steel